Household structure in the EU - Maria Iacovou; Alexandra Skew (University of Essex, Institute for Social and Economic Research (ISER), 2010)
This paper maps key indicators of household structure across all countries for all countries of the expanded European Union except Malta. As well as presenting statistics which take the entire household as the unit of analysis, we also focus on groups which are particularly interesting in terms of social policy, and for whom household composition may be particularly crucial in terms of their risk of poverty: children, young adults and elderly people. A main aim of the paper is to discuss the extent to which the new EU member states of Eastern Europe display differences and similarities with the other countries of the EU. We find that the Eastern European countries are rather heterogeneous. The Czech Republic and Hungary are not dissimilar to the countries of North-Western Europe; by contrast, households in Slovenia, Slovakia and Poland closely resemble Southern European households. Finally, it is the Baltic states - particularly Latvia - where household structure least resembles structures in any of the pre-enlargement EU countries.
Keywords: 330; household; family; Europe; Privater Haushalt; Familie; EU-Staaten